Improved Therapeutic Effect of Puerarin-Encapsulated PEG-PLGA Nanoparticle on an In Vitro Cerebral Infarction Model - Lei Li; Yan Li; Cheng Miao; Rui Liu (Advances in Polymer Technology)
This study was to explore the therapeutic effect and mechanism of puerarin (PUE) combined with PEGylated nanoparticles on a rat cerebral infarction cell model. In this context, PEG-PLGA/PUE nanoparticles were prepared by the thin-film hydration method, and the toxicity of PEG-PLGA/PUE nanoparticles to brain capillary endothelial cell (BCEC) was detected by MTT. The BCEC/TF cell model was obtained by induction of BCEC cells with TNF-α. The BCEC/TF cell model was identified by immunofluorescence; the protein expression was detected by western blotting; the expression level of miR-424 in cells was measured by RT-qPCR; the targeting relationship between miR-424 and PDCD4 was confirmed by dual-luciferase reporter assay. We found that PEG-PLGA/PUE nanoparticles prepared by the thin-film hydration method had uniform particle size, regular shape, and good stability and were not toxic to cells. The vWF was widely expressed in the cytoplasm in BCECs. The BCEC/TF cell model was obtained after TNF-α treatment, and tissue factor (TF) was widely expressed on the cell membrane of BCEC/TF cells. Furthermore, it was observed that the PEG-PLGA/PUE nanoparticles showed better therapeutic effect on the BCEC/TF cell model than PUE. PEG-PLGA/PUE nanoparticles and PUE inhibited the expression of PDCD4 protein by increasing the expression of miR-424 in BCEC/TF cells. In summary, the therapeutic effect of PEG-PLGA/PUE nanoparticles on the in vitro cell model of cerebral infarction is better than that of PUE. Moreover, PEG-PLGA/PUE inhibits the expression of PDCD4 protein by lowering the expression level of miR-424 in cells, thereby reducing the hazard of cerebral infarction.